2012
DOI: 10.1080/13645579.2012.688319
|View full text |Cite
|
Sign up to set email alerts
|

Using elderly data theoretically: personal life in 1949/1950 and individualisation theory

Abstract: The use of secondary data in sociological research has attracted much critique. For some commentators, problems are so severe that the use of secondary data is greatly compromised, perhaps best avoided. For others, these issues do not seem particularly severe and, sometimes, the objections seem misplaced. I review these problems and their resolutions, illustrated by my own research on personal life in 1949/1950 -which I undertook to assess the assumption of 'traditional society' made by individualisation theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This trend in data reuse has also been driven by innovation in early methodological advances that facilitated multiple interpretations of the same data (Holland et al, 2006). The varied and creative ways in which existing data are being re-constructed and re-contextualized to produce new insights and knowledge stand testament to the social scientific value of QSA (see, for example, Bornat et al, 2012; Duncan, 2012; Irwin and Winterton, 2011a, 2011b; Moore, 2007; Neale, 2017; Savage, 2005). A less developed strand of this debate, however, concerns the complexities and affordances of bringing multiple datasets from different research teams into ‘meaningful analytical conversation’ and translating evidence across them (Irwin et al, 2012).…”
Section: Qsa: Our Approachmentioning
confidence: 99%
“…This trend in data reuse has also been driven by innovation in early methodological advances that facilitated multiple interpretations of the same data (Holland et al, 2006). The varied and creative ways in which existing data are being re-constructed and re-contextualized to produce new insights and knowledge stand testament to the social scientific value of QSA (see, for example, Bornat et al, 2012; Duncan, 2012; Irwin and Winterton, 2011a, 2011b; Moore, 2007; Neale, 2017; Savage, 2005). A less developed strand of this debate, however, concerns the complexities and affordances of bringing multiple datasets from different research teams into ‘meaningful analytical conversation’ and translating evidence across them (Irwin et al, 2012).…”
Section: Qsa: Our Approachmentioning
confidence: 99%
“…If we had adopted a different understanding of social change our methodology would have been different; we may well have found more change than continuity, but we would then have had the problem of disentangling what was due to ‘real’ social change and what was a product of our changed methodology. The only way round this would have been to reanalyse the raw data from the 1960 study although this would have presented other methodological problems (Savage, 2005; Gillies, 2008; Duncan, 2012). We suggest that our adoption of this ‘old fashioned’ conceptual framework has provided a more accurate picture of the continuities in how people live their lives than we would have presented had we departed from the theoretical framework of the original study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that such theories may owe more to the preoccupations and experiences of sociologists than to epochal changes in society (Savage, 2005(Savage, , 2010; Duncan and Smith, 2006). Indeed, much research on families and personal life suggests that these 'grand narratives' of social change do not explain the ways in which people go about their daily lives and demonstrates the continuing importance of both family and social relations rooted in place (see, eg, Duncan andSmith, 2002, 2006;Mason, 2004;Charles and Davies, 2005;Smart, 2007;Savage, 2005). Community studies, rather than developing grand theory to explain societal change, show how lives are lived in the context of wider social change; they provide case studies which can 'illuminate the general' (Frankenberg, 1990;Charles and Davies, 2005) and 'be used to elaborate wider analytical themes' (Morgan, 2008: 30).…”
mentioning
confidence: 99%
“…The interest in data sharing is growing internationally (Neale and Bishop, 2010). There is a growing body of work that stands testimony to the research potential of secondary analysis (just a tiny handful of examples might include: Savage, 2005;Duncan, 2012;Haynes and Jones, 2012; and, we hope, the secondary analysis work undertaken as part of ESRC Timescapes 1 ). The papers in this Open Space collection are a new and powerful further addition to a growing body of work, and exemplify secondary analysis in practice.…”
mentioning
confidence: 99%